An updated synopsis of Neurolaena (Neurolaeneae, Asteraceae) with a new species from the Colombian Andes - Bueno, Vinicius R.; Gostel, Morgan R.; Heiden, Gustavo (Phytotaxa, 2023)
Neurolaena is a genus native to the Americas and occurring from Mexico to Bolivia, including the Caribbean Islands. It includes shrubs or small trees with alternate leaves, paniculiform capitulescence, discoid or radiate capitula, 3–7-seriate involucre, and pappus with 25–70 bristles. Based on recent taxonomic studies in Neurolaeneae, we provide updates for the infrageneric classification of Neurolaena and recognize the occurrence of disc florets not associated with paleae for the first time in the genus. Furthermore, we describe a new species, N. curtipalea, which is the second species of the genus found in South America and the only species endemic to the Colombian Andes. It can be distinguished from the widespread N. lobata, occurring from Mexico to Bolivia and across the Caribbean Islands, by eucamptodromous (vs. penninervous) venation, radiate (vs. discoid) capitula, 5-seriate (vs. 6-seriate) involucre, paleae shorter (vs. longer) than corolla disc, and disc florets with white (vs. yellow) corollas. The new species is described, illustrated, and mapped, its taxonomic affinities are discussed, and a key to the infrageneric taxa and species belonging to Neurolaena is provided.